The Effect of Applying Practical Work Using the Kitchen Preparation Technique to Improve Students' Concept Mastery on the Topic of Hereditary Substances - Ashari, Panji (Asian Journal of Science Education, 2024)
The purpose of this study is to investigate how students' conceptual comprehension is affected when the "kitchen preparation" approach is applied in the DNA isolation practicum. A quasi-experimental design with a pretest-posttest control group is the study methodology employed. Students from MAN 1 Banda Aceh's 12th grade, split into experimental and control groups, made up the research sample. While the control group engaged in traditional learning, the experimental group underwent treatment in the form of a practicum in kitchen preparation. The results of the hypothesis test demonstrated a significant difference in conceptual understanding between the experimental and control groups, with a p-value of 0.01 (p0.05). This suggests that students' conceptual understanding is positively impacted by the application of the kitchen preparation technique in the DNA isolation practicum. This study confirms the value of including straightforward, affordable, and pertinent practicums in biology education, particularly for intricate subjects like genetic materials